Encroachment on the Ghats - Ghosh, Ayan (2023)
Over the years, there has been a lot of encroachment on and around the Banganga Tank that has considerably altered the size, ambience, and historicity of the sites. It is due to the activism of citizen groups who were concerned about the deterioration of the tank that the Banganga complex was declared a heritage zone in April 1995 under a notification of the Urban Development Department of the Government of Maharashtra, known as the Heritage Regulations for Greater Bombay 1995.